Synergizing hole accumulation and transfer on composite Ni/CoOx for photoelectrochemical water oxidation. Issue 70 (4th August 2020) - Wang, Wei; Heggen, Marc; Cui, Wei; Probst, Benjamin; Alberto, Roger; Cui, Chunhua
Abstract : Ni/CoO x sites were supported on an around 2 nm-TiO x modified hematite photoanode for water oxidation. Abstract : Ni/CoO x sites were supported on an around 2 nm-TiO x modified hematite photoanode for water oxidation. TiO x demonstrates insignificant hole accumulation and a catalytically inactive surface that serves as an ideal platform. We reveal that the NiO x favors the extraction of holes from the TiO x surface, which are efficiently transferred to active CoO x for water oxidation.